Methods for Surveying Stable Fly Populations. Issue 6 (2nd November 2020) - Taylor, David B; Harrison, Kyle; Zhu, Junwei J
Abstract: Stable flies are among the most important pests of livestock throughout much of the world. Their painful bites induce costly behavioral and physiological stress responses and reduce productivity. Stable flies are anthropogenic and their population dynamics vary depending on agricultural and animal husbandry practices. Standardized sampling methods are needed to better identify the factors controlling stable fly populations, test novel control technologies, and determine optimal management strategies. The current study reviewed methods used for a long-term study of stable fly population dynamics in the central Great Plains. An additional study compared the relative size of flies sampled from the general population with that of flies sampled emerging from substrates associated with livestock production. Flies developing in livestock associated substrates are significantly larger than those in the general population indicating that other types of developmental sites are contributing significant numbers of flies to the general population. Because efforts to identify those sites have yet to be successful, we speculate that they may be sites with low densities of developing stable flies, but covering large areas such as croplands and grasslands. The stable fly surveillance methods discussed can be used and further improved for monitoring stable fly populations for research and management programs.